Continuous Cropped Winter Wheat in Southeast Kansas - Fausett, Marvin R. (My University, 1995)
This publication outlines the expected costs and returns for continuous cropped winter wheat in southeast Kansas.
MF992_1995_10
Keywords: MF992; Economics; Crops; MF